Physical Activity Patterns and Factors Related to Exercise during Pregnancy: A Cross Sectional Study - Nascimento, Simony Lira; Surita, Fernanda Garanhani; Godoy, Ana Carolina; Kasawara, Karina Tamy; Morais, Sirlei Siani (PLOS ONE, 2015)
Objective To assess the physical activity levels of pregnant women and to examine the characteristics associated with the practice of exercise and the activities of daily living during pregnancy. Methods For this cross-sectional study, 1,279 women were recruited within 72 hours postpartum. They were interviewed about their socio-demographic data and obstetric history and were administered self-report questionnaires about exercise and daily physical activities during pregnancy. Data on the current pregnancy, labor, delivery, and newborn outcomes were collected from participants’ medical records. To analyze factors related to the practice of exercise, we used the student t-test, X², and odds ratio (OR), with a corresponding 95% confident interval (CI), followed by a multiple logistic regression. The significance level was 5%. Results Compared to the pre-pregnancy period, the prevalence of physical activity among participants was lower throughout pregnancy (20.1%) (p = 0.01). Half of the women interrupted practicing physical exercise due to pregnancy. The lowest prevalence of exercise was observed in the first (13.6%) and third trimesters (13.4%). Less than half of women received exercise guidance during prenatal care meetings (47.4%). Walking was the most commonly reported exercise, followed by water aerobics. Factors positively associated with exercise practice were higher educational level (OR= 1.82; CI 95% 1.28–2.60), primiparity (OR=1.49; CI 95% 1.07–2.07), exercising before pregnancy (OR= 6.45; CI 95% 4.64–8.96), and exercise guidance during prenatal care (OR=2.54; CI 95% 1.80–3.57). Mildly intense exercise and domestic activities were most frequently reported among pregnant women. There were no differences in maternal and perinatal outcomes between active and sedentary pregnant women. Conclusion The findings indicate that promoting physical activity remains a priority in public health policy, and women of childbearing age, especially those planning a pregnancy, should be encouraged to adopt an exercise routine or maintain an active lifestyle during pregnancy in order to avoid sedentary- and obesity-associated risks.